2016
DOI: 10.4329/wjr.v8.i3.316
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography features of pancreatic metastases from leiomyosarcoma: Experience at a tertiary cancer center

Abstract: AIM:To describe the multidetector computed tomography features of pancreatic metastasis from leiomyosarcoma (LMS). METHODS:Between January 1995 and December 2012, 13 consecutive patients (11 women, 2 men; mean age of 57 years; range, 38-78 years) with pancreatic metastases from LMS were included in our study. Imaging features including location, number, largest dimension, tumor attenuation and enhancement characteristics, presence of necrosis, pancreatic ductal dilatation, common bile duct (CBD) dilatation, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…A literature review of LMS metastasis to the pancreas is presented in Table 1 [6][7][8][9][10][11][12][13]. A retrospective study of 13 patients with metastatic pancreatic LMS showed that the median interval between diagnosis of metastases and primary LMS was 24 moths (range, 1-77 moths), and all patients were associated with metastases to other organs [14]. In this case, pancreatic and thigh metastasis were found 3 years after resection of the broad ligament LMS, showing a long interval between the treatment of primary LMS and the appearance of pancreatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review of LMS metastasis to the pancreas is presented in Table 1 [6][7][8][9][10][11][12][13]. A retrospective study of 13 patients with metastatic pancreatic LMS showed that the median interval between diagnosis of metastases and primary LMS was 24 moths (range, 1-77 moths), and all patients were associated with metastases to other organs [14]. In this case, pancreatic and thigh metastasis were found 3 years after resection of the broad ligament LMS, showing a long interval between the treatment of primary LMS and the appearance of pancreatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic pancreatic LMS has no specificity in clinical and image findings, so it is difficult to make an exact diagnosis preoperatively. In contrast-enhanced CT scan, most of metastatic pancreatic LMSs are hypovascular [14], which need to be carefully differentiated from pancreatic ductal adenocarcinoma. In this case, the pancreatic lesion showed heterogeneous enhancement that was lower than the surrounding normal pancreas in arterial phase, and the same enhancement degree with the surrounding tissue in venous phase.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic adenocarcinoma generally remains hypoechoic, but an almost black echo texture, round appearance with sharply defined borders should raise a possibility of some other lesion as seen in these two cases. According to a study by Suh et al 4…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al 22 reported that on ultrasound, SCAs usually have more than six loculi that are less than 2 cm in diameter. Bhatt and Vaishnav 23 found that SCAs were approximately 5 cm–6 cm in size with small internal cysts < 2cm, with septations. However, Curry et al 24 reported that the largest cyst in each tumour was smaller than 2 cm in only 14 (64%) out of the 22 patients.…”
Section: Discussionmentioning
confidence: 99%